Sosialisasi Penanganan Stunting Sebagai Upaya Sustainable Development Goals Desa Keban Agung - Jody Afif Setiawan; Ramona Preselia; Lulu Artafia; Rahmad Iman; Reigah W Andrean; Hezron Swandi; Julfitri Siregar; Distri Imelia; Cindi Konera; Barika Barika (UNIB Press, 2022)
Prevention of stunting in children in Indonesia still needs attention, including Bengkulu. One form of stunting prevention activity is through community service activities. This service activity is in the form of socialization about stunting prevention in Keban Agung Village, Seluma Regency. The purpose of implementing stunting socialization is to provide self-awareness to villagers about the importance and dangers of stunting. The method used is observation and socialization about stunting. The results obtained are that the residents of Keban Agung Village receive early knowledge and awareness to prevent stunting in children and are aware of implementing a healthy lifestyle to avoid stunting and other diseases.